1984
DOI: 10.1073/pnas.81.10.3103
|View full text |Cite
|
Sign up to set email alerts
|

Fc-mediated binding of IgG to vimentin-type intermediate filaments in vascular endothelial cells.

Abstract: Prior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Centriole staining was not observed, when preabsorbed anti-tektins were used. Hansson et al (27) (data not shown) similar to those described for uncleaved anti-tektins.…”
Section: Resultssupporting
confidence: 61%
“…Centriole staining was not observed, when preabsorbed anti-tektins were used. Hansson et al (27) (data not shown) similar to those described for uncleaved anti-tektins.…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, our current findings represent a plausible explanation for our previous demonstration of increased expression of PAI-1 on the surface of endothelium exposed to bacterial endotoxin and other inflammatory mediators in vitro (57) and in vivo (34). Vimentin also may modulate inflammatory responses and atherosclerosis (58) through its interactions with plasma proteins such as complement (59,60), IgG (61,62), and fibrinogen (62). Cytokeratin-type intermediate filaments that are also exposed on the surface of various cells interact with various hemostasis factors including kininogen (63,64), plasminogen (65), and thrombin⅐antithrombin⅐Vn complexes (66).…”
Section: Table I Pai-1 Activity and Antigen In Thrombin-activated Plamentioning
confidence: 54%
“…Endothelial cell damage has been reported to result from circulating pathologic autoantibodies against EC [6,7]. Passive accumulation of normal IgG has been found only in irreversibly damaged EC [8].…”
Section: Introductionmentioning
confidence: 99%